Architecture now 6! - Jodidio, Philip, 1954- (Köln : Taschen, 2009)
An up-to-the-minute reference work of contemporary architecture. This sixth installment of Architecture Now! features buildings ranging from Fujimori's tiny (6.07 sq meters) Teahouse Tetsu to Foster's gigantic Crystal Island in Moscow (1.1 million sq meters), providing an arching overview of today's architecture, from traditional to radically avant-garde. What is the zeitgeist, and whither architecture in this new century? Architecture Now! 6 is the reference for what's happening now and what's to come. Easy-to-navigate illustrated A-Z entries include current and recent projects, biographies, contact information, and websites. Featured architects/firms/artists: 3deluxe, 3LHD Architects, Adjaye/Associates, Ai Wei Wei/FAKE Design, Tadao Ando, Alejandro Aravena, ARGE Grazioli Krischanitz, Shigeru Ban, Barkow Leibinger, Bernardes + Jacobsen, Olafur Eliasson, KSP Engel und Zimmermann, FAM Arquitectura, Foster and Partners, Terunobu Fujimori, Massimiliano Fuksas, Antón García-Abril, Dionisio González, Zaha Hadid, Heatherwick Studio, Herzog & de Meuron, Steven Holl, Holzer Kobler, Junya Ishigami, Toyo Ito, Jakob+MacFarlane, Carlos Jimenez, Kengo Kuma, Lassila Hirvilammi, Daniel Libeskind, LIN Finn Geipel + Giulia Andi, MIII Architecten, MADA s.p.a.m., Paulo Mendes da Rocha, Corinna Menn, Merkx+Girod Architecten, José Rafael Moneo, Morphosis, MvRdV, Manfredi Nicoletti, Valerio Olgiati, Studio Pei-Zhu, Renzo Piano, PTW Architects, Studio Arne Quinze, RCR Arquitectes, Rojkind Arquitectos, Marc Rolinet, Hans-Jörg Ruch, SANAA/Sejima + Nishizawa, Thomas Schütte, Scope Cleaver, Álvaro Siza Vieira, Snøhetta, Tonkin Liu, Bernard Tschumi, UNStudio, URBANUS, Pekka Vapaavuori, Various Architects, Wandel Hoefer Lorch, Jean-Michel Wilmotte, Riken Yamamoto, Peter Zumthor.
Keywords: Architectuur -- 20ste eeuw